Biodiversity and zoogeography of the Polychaeta (Annelida) in the deep Weddell Sea (Southern Ocean, Antarctica) and adjacent deep-sea basins - Schüller, Myriam (Dipl.) (2007)
Die Polychaetenproben von 29 Epibenthosschlittenstationen im tiefen Weddell Meer (Südozean) und angrenzenden Meeresbecken wurden untersucht und bezüglich ihrer Biodiversität und Zoogeographie analysiert. Insgesamt über 11.000 Individuen wurden gefunden, die zu 48 verschiedenen Familien gehören. Dreizehn Familien wurden auf Artniveau bestimmt. Dies resultierte in einer Liste von 155 verschiedenen Arten. Neubeschreibungen von 15 Arten wurden präsentiert, zudem wurde die Gattung \(\it Ammotrypanella\) revidiert und ein Bestimmungsschlüssel für die gefundenen Arten präsentiert. Die Analyse der Biodiversität zeigt, dass der Südozean eine hoch diverse Polychaetenfauna beherbergt, welche sich aus Endemiten zusammensetzt und Arten, die über einen faunalen Austausch mit angrenzenden Meeresbecken eingewandert sind. Die vertikale und globale Verbreitung der Arten wird präsentiert und diskutiert. The polychaete samples of 29 epibenthic sledge stations in the deep Weddell Sea (Southern Ocean) and adjacent basins have been observed and analyses on biodiversity and zoogeography have been carried out. A total of over 11,000 specimens were found in these samples belonging to 48 different polychaete families. Thirteen families have been identified to species level resulting in a list of 155 different species. The descriptions of 15 new species are given within this study. In addition, the genus \(\it Ammotrypanella\) is revised and an identification key to all species found is presented. The analysis of the biodiversity has proven the Southern Ocean to host a highly diverse polychaete fauna consisting of endemic species and species resulting from a faunal exchange to adjacent basins. The vertical and global distribution of species is presented and discussed.